A 10 s: 5 s high-intensity interval training regime improves rowing performance in varsity and international class rowers - Reid, B. J. (The University of Western Ontario, 2023)
The purpose of this study was to investigate the effects of a high-intensity interval training regime with elite collegiate rowers on their rowing performance. A total of 10 interval training sessions were performed over a four-week period with four males and five females completing all pre-testing performance and training sessions. Participants completed a 2000 m performance test to determine initial training intensity. The interventional training sessions consisted of 30 min of 10 s work: 5 s recovery. The 10 s mean power output improved 17% from training session one to ten. The moderate intensity increased by 44%; mean power output over 30 min increased by 22%. Three participants that performed a post-testing 2000 m row improved their power output by 3%. This study has demonstrated that 10 sessions of a 10 s: 5 s training regime improved training performances as well 2000 m in select elite rowers.